Modeling the process of filtration of a fluid from a multicomponent pollution by a spatial filter under the condition of identification of the mass-exchange coefficient - Bomba, A.Ya.; Safonyk, A. P. (Reports of the National Academy of Sciences of Ukraine, 2014)
The problem of modeling of the process of purification of liquids from a multicomponent pollution by a spatial filter is considered. The influence of the determining factors (concentrations of the contamination and the sediment) on the environmental characteristics (porosity coefficient, diffusion) is taken into account. The problem provides the opportunity for the definition of a small mass exchange factor under conditions of domination of convective constituents over diffusive ones. An algorithm of solution the corresponding nonlinear inverse singularly perturbed task of the convection–diffusion–mass exchange type is proposed.